Life and efficiency of incandescent lamps - Bender, Louis Blaine; Davis, William DeOzro (My University, 1904)
Introduction: The intelligent selection and proper use of incandescent lamps largely determine the volume and growth of the electric lighting industry. Nothing produces such radical improvement in the lighting service as, first, the exclusive use of the best lamps and, second, the frequent and regular renewal of dim lamps. These principles are the precepts and practice of the leading central stations of the country, and should be law for every electric lighting company. Central stations are in the business of making and selling light. They may sell by the Watt hour or by contract, but, regardless of the way it is measured, the customer is in reality buying and using light. Since the lamp transforms the electrical energy of the generators into light, the best lamp is an absolute necessity to obtain the best light. It is, then, almost a self-evident truth that the exclusive use of the best lamps is the only means of obtaining the best results.
Citation: Bender, Louis Blaine and Davis, William DeOzro. Life and efficiency of incandescent lamps. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Incandescent Lamps; Electricity; History of Electricity; Technological Advancement; Theses